Unravelling Qur'anic Arabic Puns Through AI English Translation And The Art Of Human Post-Editing - Albalawi, Abdulrahman Fahad; Abdul Ghafour, Abdul Qader Khaleel (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study investigates the intricate realm of puns, a linguistic feature characterized by its multifaceted meanings and significant role in enriching religious texts. Puns present a unique challenge in translation, especially within the context of the Holy Qur'an. To examine these challenges, this study employed Newmark's approach, selecting ten purposive puns from the Holy Qur'an for analysis. AI first translated each selected pun and then subjected to two rounds of editing by professional translators to enhance linguistic precision and stylistic elegance. A qualitative analysis was conducted to assess the extent to which the AI-generated and post-editing translations captured the intended meanings of the puns. The findings reveal that while AI translations provide a competent foundational interpretation of the text, they often need more depth to fully encapsulate the puns' dual or layered meanings. Human post-editing significantly refines these translations, enhancing linguistic accuracy and embracing the puns' aesthetic and theological richness. However, the accuracy in conveying the puns' intended meanings varied, with not all post-edited translations fully capturing the intricate balance of literal and metaphorical interpretations. The study underscores the vital synergy between AI and human expertise in achieving translations that balance accuracy with aesthetic appeal.